2023
DOI: 10.1101/2023.01.24.525436
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Immune-Related Candidate Biomarkers in Plasma of Patients with Sporadic Vestibular Schwannoma

Abstract: Vestibular schwannoma (VS) is intracranial tumor arising from neoplastic Schwann cells, causing hearing loss in about 95% of patients. The traditional belief that hearing deficit is caused by physical expansion of the VS, compressing the auditory nerve, does not explain the common clinical finding that patients with small tumors can have profound hearing loss, suggesting that tumor-secreted factors could influence hearing ability in VS patients. Here, we conducted profiling of patients plasma for 67 immune-rel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Clustering heatmaps and volcano plots revealed that all the differentially expressed proteins tended to be upregulated in the relapse group and severe attack group (Figures 1D,E and 2B,C). These proteins have all been reported to be related to the occurrence and development of neuroinflammatory diseases and the proliferation of various immune cells 16–27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clustering heatmaps and volcano plots revealed that all the differentially expressed proteins tended to be upregulated in the relapse group and severe attack group (Figures 1D,E and 2B,C). These proteins have all been reported to be related to the occurrence and development of neuroinflammatory diseases and the proliferation of various immune cells 16–27 …”
Section: Resultsmentioning
confidence: 99%
“…These proteins have all been reported to be related to the occurrence and development of neuroinflammatory diseases and the proliferation of various immune cells. [16][17][18][19][20][21][22][23][24][25][26][27]…”
Section: Identification Of Differentially Expressed Inflammatory Prot...mentioning
confidence: 99%